Negative electrode for soft package cylindrical battery and preparation method of negative electrode
By using foam copper current collector and porous carbon nanomaterials in soft-pack cylindrical batteries, combined with the application of surfactant, the problems of poor wetting and low rate performance of traditional negative electrodes in soft-pack cylindrical batteries are solved, and high energy density is achieved and good cycle stability.
Patent Information
- Application Number
- CN202411322572.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The negative electrode of traditional lithium-ion batteries has problems such as poor wetting and low rate performance in soft-pack cylindrical batteries, and the existing improvement methods have defects in cost and adaptability, making it difficult to meet the requirements of high performance and large-scale production.
Using foam copper current collector as the negative electrode material, combined with graphite, conductive carbon black, porous carbon nanomaterials and surfactants, the negative electrode slurry is prepared by plasma treatment, step-by-step mixing and vacuum impregnation to enhance the conductivity and wetting performance of the electrode. .
It significantly improves the energy density, rate performance and cycle stability of the battery, simplifies the infiltration process of the electrolyte, reduces the interface resistance, and improves the conductivity and structural stability of the negative electrode.
Smart Images

Figure CN119297204A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode for a soft-package cylindrical battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and environmental friendliness. As the market continues to increase its requirements for battery performance and shape diversity, soft-pack cylindrical batteries have attracted more and more attention because they combine the advantages of cylindrical batteries and soft-pack batteries. However, the development of high-performance negative electrode materials and structures suitable for soft-pack cylindrical batteries still faces many challenges.
[0003] Traditional lithium-ion battery negative electrodes usually use graphite materials coated on copper foil current collectors. This structure has the following problems when applied to soft-pack cylindrical batteries: first, flat copper foil is difficult to adapt to the cylindrical shape, and it is easy to produce wrinkles and stress concentration during the winding process, affecting the safety and cycle performance of the battery; second, the poor wettability of the traditional negative electrode makes it difficult for the electrolyte to quickly and evenly penetrate into the electrode in the cylindrical shape, affecting the production efficiency and performance of the battery; third, the lithium ion diffusion path of the conventional negative electrode structure is long, which limits the battery's rate performance and fast charging ability. This problem is more prominent in the cylindrical shape.
[0004] To solve these problems, researchers have tried a variety of methods, such as using flexible current collectors, improving binder systems, etc. However, these methods often have disadvantages such as poor adaptability, high cost, or difficulty in large-scale production when applied to soft-pack cylindrical batteries. Therefore, developing a negative electrode structure that combines high performance, good flexibility, and mass production, especially a negative electrode structure suitable for soft-pack cylindrical batteries, remains an important challenge.
[0005] In recent years, three-dimensional porous current collectors have attracted the attention of researchers. Among them, metal foams have become potential candidate materials for the negative electrode of soft-pack cylindrical batteries due to their high porosity, large specific surface area, good conductivity and flexibility. However, how to effectively and evenly distribute the active materials in the pores of metal foams while ensuring high capacity, good conductivity, excellent wettability and appropriate flexibility of the electrode is still a technical problem that needs to be solved urgently.
[0006] In addition, the traditional negative electrode preparation process is difficult to adapt to the special structure of the three-dimensional porous current collector, and it is even more difficult to meet the special requirements of the soft-pack cylindrical battery. It is necessary to develop a new preparation method to give full play to its advantages. Especially in terms of wetting performance, how to ensure the high capacity of the electrode while achieving rapid and uniform infiltration of the electrolyte in the cylindrical shape is the key to improving the production efficiency and performance of soft-pack cylindrical batteries.
[0007] Therefore, developing a high-performance negative electrode for soft-pack cylindrical batteries based on a three-dimensional porous current collector and designing a matching preparation process have important theoretical significance and practical application value. Summary of the invention
[0008] The main purpose of the present invention is to provide a negative electrode for a soft-pack cylindrical battery in view of the shortcomings of the prior art, which can effectively solve the problems of poor wettability and low rate performance of the negative electrode of the soft-pack cylindrical battery.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] A negative electrode for a soft-package cylindrical battery comprises a foam copper current collector and a negative electrode active material layer coated on the foam copper current collector; the negative electrode active material layer comprises the following components in parts by weight:
[0011] Graphite 95-105 parts;
[0012] Conductive carbon black 1-5 parts;
[0013] Binder SBR 1-5 parts;
[0014] Dispersant CMC 0.5-2.5 parts;
[0015] Wetting agent SFC 0.1-1 part;
[0016] 1-5 parts of porous carbon nanomaterial;
[0017] Surfactant 0.1-0.5 parts.
[0018] Among them, the foam copper current collector has a high specific surface area and a three-dimensional network structure, which is not only conducive to the infiltration of the electrolyte, but also can load more active materials and is conducive to the uniform distribution of active materials. It can shorten the transmission path of electrons and ions, reduce the interface resistance, and improve the energy density and rate performance of the battery.
[0019] Among them, the wetting agent SFC is an anionic polymer emulsion produced by Shanghai Daoying Industrial Co., Ltd. The anionic macromolecules in it have an affinity with the electrolyte on the surface of the negative electrode sheet and can effectively lock the electrolyte, thereby improving the liquid retention and wetting properties of the negative electrode.
[0020] Preferably, the density of the foam copper current collector is 0.45-0.65 g / cm³, the porosity is 85-95%, the pore size is 200-500 μm, the specific surface area is 1500-2500 cm² / g, and the thickness is 0.8-1.2 mm.
[0021] Preferably, the graphite is a mixture of artificial graphite and natural graphite, wherein the weight ratio of artificial graphite to natural graphite is (3-4):1.
[0022] Preferably, the porous carbon nanomaterial is a mixture of carbon nanotubes and graphene, wherein the weight ratio of the carbon nanotubes to the graphene is (1-2):1.
[0023] Preferably, the surfactant is sodium dodecylbenzene sulfonate.
[0024] Preferably, the surfactant is perfluorooctane sulfonate (PFSA) and C2F5CONH(CH2CH2O) 23 A mixture of COC2F5, wherein ammonium perfluorooctane sulfonate (PFSA) and C2F5CONH (CH2CH2O) 23 The mass ratio of COC2F5 is 1:(1~2).
[0025] Preferably, the surface density of the negative electrode active material layer is 20-25 mg / cm².
[0026] Preferably, the area specific capacity of the negative electrode is 6-8 mAh / cm².
[0027] In addition, the present invention also provides a method for preparing the above-mentioned negative electrode for the soft-package cylindrical battery, comprising the following steps:
[0028] (1) Plasma treatment of the surface of the foam copper current collector;
[0029] (2) mixing the conductive carbon black, CMC and deionized water, and stirring and dispersing them at 2000-3000 rpm for 80-120 min at 20-25° C.;
[0030] (3) adding SBR, graphite and porous carbon nanomaterial to the mixture of step (2), and continuing to stir and mix at a speed of 2000-3000 rpm at 20-25° C. for 80-120 min;
[0031] (4) adding a wetting agent SFC and a surfactant to the mixture of step (3), continuing to stir and mix at a speed of 700-900 rpm at 20-25° C. for 60-80 min, controlling the solid content to 45-50%, and obtaining a negative electrode slurry with a viscosity of 2000-3500 mPa·s;
[0032] (5) coating the negative electrode slurry on the surface-treated copper foam current collector, and using a vacuum impregnation method to allow the negative electrode slurry to fully penetrate into the pores of the copper foam;
[0033] (6) Drying at 110-130° C. for 15-25 min;
[0034] (7) The dried negative electrode is subjected to roller pressing at a pressure of 6-10 MPa to obtain a negative electrode.
[0035] In the preparation method of the negative electrode, the foam copper current collector is subjected to plasma treatment, which can modify its surface, increase the surface roughness and hydrophilicity, enhance the binding force between the current collector and the active material, and improve the structural stability of the negative electrode; the preparation process of the negative electrode slurry adopts a step-by-step mixing method, first dispersing the conductive carbon black to form a conductive network, and then adding a binder, an active material, etc., to obtain a uniform and stable slurry system; vacuum impregnation coating is adopted, so that the negative electrode slurry can fully penetrate into the pores of the foam copper, increase the contact area between the active material and the current collector, and increase the loading capacity; roller pressing can improve the density and conductivity of the negative electrode, and the preferred roller pressing pressure can take into account both the densification and the integrity of the conductive network.
[0036] Preferably, the vacuum impregnation process in step (5) comprises: immersing the foam copper current collector in the negative electrode slurry, evacuating to -0.08MPa~-0.1MPa, maintaining for 5-10min, then slowly releasing the vacuum, and repeating the process 2-3 times.
[0037] Preferably, the viscosity of the negative electrode slurry in step (4) is 2500 to 3000 mPa·s.
[0038] Preferably, the method further comprises performing vacuum drying after step (7), wherein the vacuum drying temperature is 50-70° C. and the time is 4-8 hours.
[0039] Compared with the prior art, the present invention has at least the following beneficial effects:
[0040] The present invention uses copper foam as the negative electrode current collector. Compared with traditional copper foil, copper foam has a three-dimensional porous network structure and a large specific surface area, which can provide more attachment sites for negative electrode active materials, increase the loading amount of negative electrode active materials, shorten the transmission path of electrons and ions, reduce interface resistance, and improve the energy density and rate performance of the battery; at the same time, the porous structure of copper foam is conducive to the penetration and transmission of electrolyte, which can significantly improve the wetting performance of the negative electrode. In addition, copper foam also has good electrical conductivity and mechanical strength, which can improve the electrical conductivity and structural stability of the negative electrode.
[0041] 2) In the composition of the negative electrode active material layer, graphite is used as the main active material. Graphite has a high specific capacity and excellent cycle stability; the addition of conductive carbon black can improve the conductivity of the negative electrode and facilitate the electron transport of the active material; the addition of porous carbon nanomaterials can, on the one hand, construct a porous conductive network to provide a high-speed transmission channel for electrons and ions, thereby improving the conductivity and rate performance of the negative electrode; on the other hand, the introduction of carbon nanomaterials can also inhibit the agglomeration of graphite particles, increase the specific surface area of the negative electrode, and promote the infiltration of the electrolyte; SBR and CMC are used as Binders and dispersants can enhance the bonding force between graphite particles and current collectors, and make graphite evenly dispersed in the negative electrode slurry to prevent agglomeration and improve the preparation quality of the negative electrode; introducing wetting agent SFC and surfactant into the negative electrode active material layer can significantly improve the wettability of the negative electrode to the electrolyte; among them, the wetting agent SFC can reduce the surface tension of the negative electrode and increase the affinity with the electrolyte; the surfactant can greatly reduce the surface tension of the electrolyte and accelerate the penetration of the electrolyte in the pores of the negative electrode, thereby accelerating the wetting speed of the negative electrode and shortening the formation time of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Schematic diagram of the structure of the negative electrode in one embodiment of the present invention.
[0043] In the figure: 1. Foam copper current collector; 2. Negative electrode active material layer. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Please refer to the attached Figure 1 The present application provides a negative electrode for a soft-package cylindrical battery, comprising a foam copper current collector 1 and a negative electrode active material layer 2 coated on the foam copper current collector 1; the negative electrode active material layer 2 comprises the following components in parts by weight:
[0046] Graphite 95-105 parts;
[0047] Conductive carbon black 1-5 parts;
[0048] Binder SBR 1-5 parts;
[0049] Dispersant CMC 0.5-2.5 parts;
[0050] Wetting agent SFC 0.1-1 part;
[0051] 1-5 parts of porous carbon nanomaterial;
[0052] Surfactant 0.1-0.5 parts.
[0053] Among them, the foam copper current collector 1 has a high specific surface area and a three-dimensional network structure, which is not only conducive to the infiltration of the electrolyte, but also can load more active materials and is conducive to the uniform distribution of active materials, which can shorten the transmission path of electrons and ions, reduce the interface resistance, and improve the energy density and rate performance of the battery.
[0054] In one embodiment of the present application, the density of the copper foam current collector 1 is 0.45-0.65 g / cm³, the porosity is 85-95%, the pore size is 200-500 μm, the specific surface area is 1500-2500 cm² / g, and the thickness is 0.8-1.2 mm. The structural parameters of the copper foam current collector 1 are optimized, and the appropriate density, porosity, pore size and specific surface area are selected to ensure the conductivity and mechanical strength of the current collector, provide sufficient permeation channels for the electrolyte, and provide a high-load attachment base for the negative electrode active material; the preferred thickness range can make the current collector have appropriate flexibility and be easy to be wound into a column.
[0055] In one embodiment of the present application, the graphite is a mixture of artificial graphite and natural graphite, wherein the weight ratio of artificial graphite to natural graphite is (3-4): 1. By mixing artificial graphite with natural graphite, the high specific capacity of artificial graphite and the low cost advantage of natural graphite can be taken into account.
[0056] In one embodiment of the present application, the porous carbon nanomaterial is a mixture of carbon nanotubes and graphene, wherein the weight ratio of carbon nanotubes to graphene is (1-2):1. Adding porous carbon nanomaterials such as carbon nanotubes and graphene to the negative electrode can, on the one hand, construct a porous conductive network, provide a high-speed transmission channel for electrons and ions, and improve the conductivity and rate performance of the negative electrode; on the other hand, the introduction of carbon nanomaterials can also inhibit the agglomeration of graphite particles, increase the specific surface area of the negative electrode, and promote the infiltration of the electrolyte. The composite use of carbon nanotubes and graphene is preferred, which can form a line-surface conductive network between the negative electrode active particles, and can give play to the synergistic advantages of the two to obtain a better comprehensive effect.
[0057] In one embodiment of the present application, the surfactant is sodium dodecylbenzene sulfonate, which can significantly reduce the surface tension of the electrolyte, accelerate the penetration of the electrolyte in the pores of the negative electrode, thereby speeding up the infiltration speed of the negative electrode and shortening the formation time of the battery.
[0058] In one embodiment of the present application, the surfactant is perfluorooctane sulfonate (PFSA) and C2F5CONH(CH2CH2O)23 A mixture of COC2F5, wherein perfluorooctane sulfonate (PFSA) and C2F5CONH (CH2CH2O) 23 The mass ratio of COC2F5 is 1: (1~2); among which, C2F5CONH(CH2CH2O) 23 COC2F5 is 3% perhalogenated amide polyoxyethylene ester. It uses ammonium perfluorooctane sulfonate and C2F5CONH (CH2CH2O) 23 The combination of COC2F5 can produce a synergistic effect and further enhance the wetting performance of the negative electrode. Among them, the fluorine-containing group can reduce the surface tension of the electrolyte, and the polyether chain is hydrophilic. The combined effect of the two greatly improves the wettability of the electrolyte and accelerates the penetration rate of the electrolyte in the pores of the negative electrode, especially for the lyophobic negative electrode, the wetting effect is more significant. Therefore, the synergistic effect of the two surfactants can significantly reduce the surface tension of the electrolyte and improve the wetting and spreading of the electrolyte on the negative electrode; at the same time, the ether bond in the surfactant has a certain film-forming property, which can form a uniform and dense wetting layer on the surface of the negative electrode, repair the area with poor wettability of the negative electrode, and improve the utilization rate of the negative electrode.
[0059] In one embodiment of the present application, the surface density of the negative electrode active material layer 2 is 20-25 mg / cm². Controlling the surface density of the negative electrode active material layer 2 to 20-25 mg / cm² can ensure sufficient active material loading while not being too dense to hinder the infiltration of the electrolyte.
[0060] In one embodiment of the present application, the area specific capacity of the negative electrode is 6-8 mAh / cm²; a high energy density can be achieved.
[0061] In addition, the present invention also provides a method for preparing the above-mentioned negative electrode for the soft-package cylindrical battery, comprising the following steps:
[0062] (1) Plasma treatment of the surface of the foam copper current collector;
[0063] (2) mixing the conductive carbon black, CMC and deionized water, and stirring and dispersing them at 2000-3000 rpm for 80-120 min at 20-25° C.;
[0064] (3) adding SBR, graphite and porous carbon nanomaterial to the mixture of step (2), and continuing to stir and mix at a speed of 2000-3000 rpm at 20-25° C. for 80-120 min;
[0065] (4) adding a wetting agent SFC and a surfactant to the mixture of step (3), continuing to stir and mix at a speed of 700-900 rpm at 20-25° C. for 60-80 min, controlling the solid content to 45-50%, and obtaining a negative electrode slurry with a viscosity of 2000-3500 mPa·s;
[0066] (5) coating the negative electrode slurry on the surface-treated copper foam current collector, and using a vacuum impregnation method to allow the negative electrode slurry to fully penetrate into the pores of the copper foam;
[0067] (6) Drying at 110-130° C. for 15-25 min;
[0068] (7) The dried negative electrode is subjected to roller pressing at a pressure of 6-10 MPa to obtain a negative electrode.
[0069] In the preparation method of the negative electrode, the foam copper current collector is subjected to plasma treatment, which can modify its surface, increase the surface roughness and hydrophilicity, enhance the binding force between the current collector and the active material, and improve the structural stability of the negative electrode; the preparation process of the negative electrode slurry adopts a step-by-step mixing method, first dispersing the conductive carbon black to form a conductive network, and then adding a binder, an active material, etc., to obtain a uniform and stable slurry system; vacuum impregnation coating is adopted, so that the negative electrode slurry can fully penetrate into the pores of the foam copper, increase the contact area between the active material and the current collector, and increase the loading capacity; roller pressing can improve the density and conductivity of the negative electrode, and the preferred roller pressing pressure can take into account both the densification and the integrity of the conductive network.
[0070] In one embodiment of the present application, the vacuum impregnation process in step (5) includes: immersing the foam copper current collector in the negative electrode slurry, evacuating to -0.08MPa~-0.1MPa, maintaining for 5-10min, then slowly releasing the vacuum, and repeating the process 2-3 times. The preferred vacuum degree and duration can ensure the adequacy of the impregnation.
[0071] In one embodiment of the present application, the viscosity of the negative electrode slurry in step (4) is 2500-3000 mPa·s.
[0072] In one embodiment of the present application, a vacuum drying process is further performed after step (7), wherein the vacuum drying temperature is 50-70° C. and the time is 4-8 hours; residual moisture can be removed, the stability of the electrode can be improved, side reactions can be reduced, and the battery life can be extended.
[0073] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.
[0074] Example 1
[0075] The present embodiment provides a method for preparing a negative electrode for a soft-package cylindrical battery, and the specific steps are as follows:
[0076] 1. Pretreatment of foam copper current collector
[0077] Copper foam with a density of 0.55 g / cm³, a porosity of 90%, a pore size of 300 μm, a specific surface area of 2000 cm² / g, and a thickness of 1.0 mm was selected as the current collector. The surface of the copper foam was treated with oxygen plasma, and the treatment parameters were: power 500 W, treatment time 5 minutes, oxygen flow rate 50 sccm, and pressure 10 Pa.
[0078] 2. Preparation of negative electrode slurry
[0079] (1) Mix 3 g of conductive carbon black, 1.5 g of CMC and 95 g of deionized water, and stir and disperse them at 2500 rpm at 23 °C for 100 min;
[0080] (2) adding 3 g of SBR, 100 g of graphite (75 g of artificial graphite and 25 g of natural graphite) and 3 g of porous carbon nanomaterial (2 g of carbon nanotubes and 1 g of graphene) to the above mixture, and stirring and mixing the mixture at 23 °C and 2500 rpm for 100 min;
[0081] (3) 0.5 g of a wetting agent SFC and 0.3 g of a surfactant (sodium dodecylbenzene sulfonate) were added to the above mixture, and the mixture was stirred and mixed at 800 rpm for 70 min at 23 °C to control the solid content to 48%, thereby obtaining a negative electrode slurry with a viscosity of 2800 mPa·s.
[0082] 3. Preparation of negative electrode
[0083] (1) coating the negative electrode slurry on the surface-treated copper foam current collector, and using a vacuum impregnation method to allow the negative electrode slurry to fully penetrate into the pores of the copper foam; wherein the vacuum impregnation process is as follows: immersing the copper foam current collector in the negative electrode slurry, evacuating to -0.09 MPa, maintaining for 8 minutes, and then slowly releasing the vacuum, and repeating the process 3 times;
[0084] (2) Dry at 120°C for 20 min;
[0085] (3) The dried negative electrode is subjected to roller pressing at a roller pressing pressure of 8 MPa;
[0086] (4) Perform vacuum drying at 60°C for 6 h to obtain a negative electrode.
[0087] Among them, the negative electrode active material layer density of the obtained negative electrode is 22.5 mg / cm², and the area specific capacity of the negative electrode is 7.2 mAh / cm².
[0088] Example 2
[0089] The difference from Example 1 is that the surfactant is perfluorooctane sulfonate (PFSA) and C2F5CONH (CH2CH2O) 23 The mixture of COC2F5 has a mass ratio of 1:1.5 and a total amount of 0.3g.
[0090] The rest is the same as in Example 1 and will not be described again here.
[0091] Example 3
[0092] The difference from Example 1 is that the density of the foam copper current collector is 0.50 g / cm³, the porosity is 92%, and the pore size is 350 μm.
[0093] The rest is the same as in Example 1 and will not be described again here.
[0094] Example 4
[0095] The difference from Example 1 is that the surfactant is perfluorooctane sulfonate (PFSA) and C2F5CONH (CH2CH2O) 23 The mixture of COC2F5 has a mass ratio of 1:1.5 and a total amount of 0.3g; the density of the foam copper current collector is 0.50 g / cm³, the porosity is 92%, and the pore size is 350 μm.
[0096] The rest is the same as in Example 1 and will not be described again here.
[0097] Comparative Example 1
[0098] The negative electrode preparation method is the same as that of Example 1, except that conventional copper foil is used instead of the foam copper current collector.
[0099] Comparative Example 2
[0100] The negative electrode preparation method is the same as that in Example 1, except that the porous carbon nanomaterial and the surfactant are not added.
[0101] Comparative Example 3
[0102] The negative electrode preparation method is the same as that of Example 1, except that the vacuum impregnation method is not used to allow the negative electrode slurry to fully penetrate into the pores of the foamed copper.
[0103] The negative electrode and positive electrode prepared in the above embodiments and comparative examples are combined to make a soft-pack cylindrical battery; wherein the positive electrode is made of NCM811 positive electrode active material, and the separator is made of PE separator. The positive electrode, separator and negative electrode are wound into a roll core, placed in an aluminum-plastic film, packaged using a heat sealer, and injected with electrolyte (1M LiPF6 EC / DMC / EMC=1:1:1) to obtain a soft-pack cylindrical battery.
[0104] The following electrochemical performance tests were performed on the negative electrodes and batteries prepared in the examples and comparative examples, respectively. The test results are shown in Table 1.
[0105] 1. Wetting performance test: Cut the prepared negative electrode into a 5 cm × 5 cm square, place it in 50 mL of electrolyte (EC: DMC: EMC = 1:1:1, volume ratio), and record the time required for the electrolyte to completely soak the negative electrode.
[0106] 2. Rate performance test: Carry out charge and discharge tests at 0.2C and 5C rates, and record the discharge capacity at each rate.
[0107] 3. Cycle performance test: Perform 500 cycles of charge and discharge test at 1C rate and record the capacity retention rate.
[0108] Table 1
[0109] The test results in Table 1 are analyzed as follows:
[0110] 1. Comparative analysis of experimental results of embodiments and comparative examples
[0111] 1) Wetting performance: The wetting time of Examples 1-4 is significantly shorter than that of Comparative Examples 1-3. This indicates that the foam copper current collector structure, the addition of surfactants, and the application of the vacuum impregnation method of the present invention significantly improve the wetting performance of the negative electrode.
[0112] 2) Rate performance: At 0.2C and 5C rates, the discharge capacities of Examples 1 to 4 are higher than those of Comparative Examples 1 to 3. In particular, at a high rate of 5C, the capacity retention of the Examples is significantly better than that of the Comparative Examples, indicating that the negative electrode structure of the present invention is conducive to improving the rate performance of the battery.
[0113] 3) Cycle performance: The capacity retention rate of Examples 1-4 after 500 cycles is significantly higher than that of Comparative Examples 1-3, indicating that the negative electrode structure of the present invention has better cycle stability.
[0114] In summary, the present invention successfully solves the problems of poor wettability and low rate performance of the negative electrode of soft-pack cylindrical batteries by adopting foam copper current collectors, adding porous carbon nanomaterials and surfactants, and using a vacuum impregnation method, while improving the cycle stability of the battery.
[0115] 2. Comparative analysis of experimental results between various embodiments
[0116] Ammonium perfluorooctanesulfonate and C2F5CONH(CH2CH2O) used in Example 2 23 The COC2F5 mixture is more effective as a surfactant than the sodium dodecylbenzene sulfonate in Example 1, significantly improving the wetting properties and electrochemical performance.
[0117] The foam copper current collector with higher porosity and larger pore size used in Example 3 also brings about performance improvement compared with Example 1, especially in terms of rate performance.
[0118] Example 4 optimizes the performance indicators of wetting performance, rate performance and cycle performance by combining the optimized surfactant of Example 2 and the improved copper foam structure of Example 3. This may be due to the combined effect of the optimized surfactant and the copper foam structure, which fully reflects the synergistic effect between these factors.
[0119] In summary, the present invention successfully developed a negative electrode for soft-pack cylindrical batteries with excellent wettability, high rate performance and good cycle stability by optimizing the foam copper current collector structure, selecting high-efficiency surfactants, adding porous carbon nanomaterials and adopting a vacuum impregnation method.
[0120] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0121] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A negative electrode for a soft-pack cylindrical battery, characterized in that: The invention comprises a foam copper current collector and a negative electrode active material layer coated on the foam copper current collector; the negative electrode active material layer comprises the following components in parts by weight: Graphite 95-105 parts; Conductive carbon black 1-5 parts; Binder SBR 1-5 parts; Dispersant CMC 0.5-2.5 parts; Wetting agent SFC 0.1-1 part; 1-5 parts of porous carbon nanomaterial; Surfactant 0.1-0.5 parts.
2. The negative electrode for a soft-package cylindrical battery according to claim 1, characterized in that: The foam copper current collector has a density of 0.45-0.65 g / cm³, a porosity of 85-95%, a pore size of 200-500 μm, a specific surface area of 1500-2500 cm² / g, and a thickness of 0.8-1.2 mm.
3. The negative electrode for a soft-package cylindrical battery according to claim 1, characterized in that: The graphite is a mixture of artificial graphite and natural graphite, wherein the weight ratio of artificial graphite to natural graphite is (3-4):
1.
4. The negative electrode for a soft-package cylindrical battery according to claim 1, characterized in that: The porous carbon nanomaterial is a mixture of carbon nanotubes and graphene, wherein the weight ratio of the carbon nanotubes to the graphene is (1-2):
1.
5. The negative electrode for a soft-package cylindrical battery according to claim 1, characterized in that: The surfactant is sodium dodecylbenzene sulfonate.
6. The negative electrode for a soft-package cylindrical battery according to claim 1, characterized in that: The surfactant is ammonium perfluorooctane sulfonate and C2F5CONH(CH2CH2O) 23 A mixture of COC2F5, wherein ammonium perfluorooctane sulfonate and C2F5CONH(CH2CH2O) 23 The mass ratio of COC2F5 is 1:(1~2).
7. The negative electrode for a soft-package cylindrical battery according to claim 1, characterized in that: The surface density of the negative electrode active material layer is 20-25 mg / cm².
8. The negative electrode for a soft-package cylindrical battery according to claim 1, characterized in that: The area specific capacity of the negative electrode is 6-8 mAh / cm².
9. A method for preparing a negative electrode for a soft-package cylindrical battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Plasma treatment of the surface of the foam copper current collector; (2) mixing the conductive carbon black, CMC and deionized water, and stirring and dispersing them at 2000-3000 rpm for 80-120 min at 20-25° C.; (3) adding SBR, graphite and porous carbon nanomaterial to the mixture of step (2), and continuing to stir and mix at a speed of 2000-3000 rpm at 20-25° C. for 80-120 min; (4) adding a wetting agent SFC and a surfactant to the mixture of step (3), continuing to stir and mix at a speed of 700-900 rpm at 20-25° C. for 60-80 min, controlling the solid content to 45-50%, and obtaining a negative electrode slurry with a viscosity of 2000-3500 mPa·s; (5) coating the negative electrode slurry on the surface-treated copper foam current collector, and using a vacuum impregnation method to allow the negative electrode slurry to fully penetrate into the pores of the copper foam; (6) Drying at 110-130° C. for 15-25 min; (7) The dried negative electrode is subjected to roller pressing at a pressure of 6-10 MPa to obtain a negative electrode.
10. The method for preparing a negative electrode for a soft-package cylindrical battery according to claim 9, characterized in that: The vacuum impregnation process in step (5) includes: immersing the foam copper current collector into the negative electrode slurry, evacuating to -0.08MPa~-0.1MPa, maintaining for 5-10min, then slowly releasing the vacuum, and repeating the process 2-3 times.
Citation Information
Patent Citations
Lithium ion battery negative electrode slurry as well as preparation method and application thereof
CN111063892A
Secondary battery and method for manufacturing same
CN113366667A
Sodium ion battery negative plate and sodium ion battery
CN116314587A
Secondary battery and electronic device
CN118073632A
Aqueous paste for forming anode active material layer of nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery anode and manufacturing method thereof, and nonaqueous electrolyte secondary battery
JP2012038597A